A pilot study: effectiveness of local injection of autologous platelet-rich plasma in treating women with stress urinary incontinence - Cheng‐Yu Long; Kun‐Ling Lin; Chin-Ru Shen; Chin-Ru Ker; Yi‐Yin Liu; Zi-Xi Loo; Hui‐Hua Hsiao; Yung‐Chin Lee (2021)
Abstract The study aims to evaluate the effectiveness of local injection of autologous platelet rich plasma (A-PRP) as a treatment for women suffering from stress urinary incontinence (SUI). In a prospective intervention study, twenty consecutive women suffering from SUI were treated with A-PRP injection at anterior vaginal wall where mid-urethra locates. Self-reported questionnaires were used to measure pre-treatment, 1 month and 6 months post-treatment symptom severity. Secondary outcomes of sexual function and treatment effect sorted by age were analyzed with valid statistical methods. A-PRP is effective in relieving SUI symptoms at both 1 month and 6 months post-treatment without significant adverse reactions reported. It seems to have a trend that treatment success rate with cured and improved symptoms was slightly higher in the younger group, although it did not reach statistical significance ( P = 0.07). No significant changes in sexual function before and after the treatment were reported by the patients. This pilot study is the first to report A-PRP treatment effect for SUI in women. The result suggested that A-PRP is a considerable treatment option for mild to moderate SUI cases. It also opens up further research opportunities for A-PRP’s clinical applications.